Repackaging authority: artificial intelligence, automated governance and education trade shows - Gulson, Kalervo N.; Witzenberger, Kevin (Journal of education policy, 2022)
Artificial Intelligence has the potential to be an important part of education governance. It is already being built into everything from business intelligence platforms to real-time online testing. In this paper, we aim to understand how AI becomes, and forms, a legitimate part of authority in contemporary education governance in what we call the automated education governance assemblage, that incorporates technology companies and AI-supported products used in education. We focus on EduTech Australia - an education technology trade show in Sydney - as a way to look at: (i) how the different aspects of automated governance are connected at EduTech, including the relations between different participants, companies and products; and (ii) how the automated governance assemblage works to legitimise and constitute EduTech as a policy space and site of new authorities in education governance.